Improving beef cattle through breeding methods - Smith, W.H.; Wheat, J.D.; Spies, H.G. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn beef cattle breeding project was continued during 1963 without modification. Inbreeding was continued in the two separate lines, which have remained closed to outside breeding since the study was initiated in 1949. The inbreeding plan has been basically to continue successive generations of half-sibbing in both lines. The Wernacre Premier line is in its fifth generation and the Mercury line, its fourth generations of inbreeding.
Keywords: Beef; Inbreeding; Production traits; Inheritance